2021
DOI: 10.3389/fmed.2021.716840
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia Predicts Adverse Outcomes After Myocardial Infarction With Non-obstructive Coronary Arteries

Abstract: Background: Serum uric acid (SUA) is a well-known predictor of adverse outcomes in patients with various clinical conditions. However, the impact of SUA on patients with myocardial infarction with non-obstructive coronary arteries (MINOCA) remains unclear. Here, we aimed at investigating the potential association between hyperuricemia and the adverse outcomes in MINOCA patients.Methods: Overall, 249 MINOCA patients were enrolled in the present study. Clinical characteristics and laboratory data, were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, further examinations of pathologies not detectable on traditional CMR is warranted. The role of CMD in MINOCA is increasingly recognized but cannot be diagnosed using traditional CMR 18 . Indeed, the workup of CMD is complex due to the many pathophysiological forms of CMD that patients present with and includes various modalities 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further examinations of pathologies not detectable on traditional CMR is warranted. The role of CMD in MINOCA is increasingly recognized but cannot be diagnosed using traditional CMR 18 . Indeed, the workup of CMD is complex due to the many pathophysiological forms of CMD that patients present with and includes various modalities 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative stress perfusion mapping can detect CMD as reduced global stress perfusion and/or myocardial perfusion reserve (MPR) 16 and can differentiate CMD from obstructive coronary artery disease (CAD) 17 . CMD has been shown in acute MINOCA and is associated with poor outcome both in the acute stage and long-term 18 . However, long-term presence of CMD following acute MINOCA presentation has to the best of our knowledge not been examined previously.…”
Section: Introductionmentioning
confidence: 97%
“…To date, limited studies with small populations have been conducted, and the results were not concordant in different subjects. Some studies have reported a correlation between UA and AMI [ 12 , 13 , 35 , 36 , 37 ]. However, it is still debatable whether hyperuricemia is an independent predictor of patients with percutaneous coronary intervention in the AMI cohort [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, data regarding the implications of HUA in MINOCA population are scarce. A recent study enrolled 249 patients with MINOCA and reported that HUA was associated with adverse outcomes [ 37 ]. Here, we addressed this issue and conducted a larger scale and longitudinal analysis of MINOCA cohort.…”
Section: Discussionmentioning
confidence: 99%